IMPLEMENTASI PENDIDIKAN MORAL SEBAGAI UPAYA PENGUATAN KARAKTER MANIUSIA DI ERA MODERN - Juwinner Kasingku; Winda Novita Warouw; Edwin Melky Lumingkewas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Moral education is an important aspect in shaping a person’s attitudes, behaviors, and decisions in daily life. The purpose of this study is to understand the role of teachers and families in developing children’s morals and character, as well as the challenges faced in the modern era. The methodology used is a qualitative approach through literature review, examining books, journals, and reliable online sources to obtain in-depth data and concepts on moral education. The results show that morals serve as a guide to distinguish right from wrong, while character is the embodiment of moral values reflected in attitudes, habits, and behaviors. Moral education in schools, through learning activities, extracurricular programs, school culture, and teacher role modeling, has proven effective in instilling positive values. Teachers act as moral and spiritual role models, guiding students to apply Christian values in their daily lives. On the other hand, families, especially parents, are the first and primary environment for moral education, playing a role through role modeling, guidance, prayer, good communication, love, and discipline. In conclusion, comprehensive implementation of moral education can shape children who are of good character, responsible, faithful, and capable of facing the challenges of the digital era, ensuring that their morals and character are consistently developed and beneficial for their social life.